Newfound Excerpts from the Nomocanon in the Synaxarion from the Andrey Sheptytsky National Museum - Chistiakova, Marina (Slavistica Vilnensis, 2020)
The article is devoted to two previously unknown excerpts from the Nomoсanon (Kormchaya), found in the late 16th century Synaxarion (or Prologue) from the Andrey Sheptytsky National Museum in Lviv, Rk 252. This manuscript contains readings from September to December and represents a specific version of the expanded edition of the Prologue, characteristic of the writing tradition of the Grand Duchy of Lithuania. The sermons, included in this copy for 17 and 25 November, are borrowed from the Nomoсanon of Fourteen Titles without commentaries, namely from the initial part of the Collection of Apostolic Rules. A comparative analysis of the articles has demonstrated that the compiler selected some successive fragments from the oldest Slavonic version of the Kormchaya and also made some omissions. The first sermon is focused on the ordination of bishops and the rules of conduct of all ranks of the clergy. The second article forbids the ordination of priests for a fee and under the auspices of the Duke. It also specifies that the bishops’ meetings should be held twice a year. A textological analysis has shown that the synaxarian sermon of 17 November had been somewhat shortened. From a linguistic point of view, excerpts from the Nomocanon bear exact correspondence to the source text. Both sermons contain brief passages from other authors and sources (St. Nilus of Sinai, the Book of Psalms, etc.). Because of the similarity in style of the work with the source, it may be assumed that extracts from the Kormchaya were simultaneously included into the Prologue by the same person, probably at a later stage of editing of this version of the Prologue. At the end of the present article, two newly discovered synaxarian articles from the Kormchaya are published.